A methodology for measuring the harm caused by organized crime - Savona, Ernesto Ugo (Improving knowledge on crime, 2009)
The present article is the third in a series of three articles by the same author in this issue of Forum on Crime and Society. This article contains a discussion on a methodology for calculating the harm caused by organized crime, harm being the second proposed element for assessing risk (the first element being the probability of organized crime occurring). In order to allow the highest degree of comparability at the international level, the proposed methodology makes use of standard data that should be easily available to policymakers. The mechanism also aims to be as simple as possible, while maintaining the capacity to deal with future developments in the fight against organized crime. A brief review of the relevant literature is provided. The meaning of the concept of harm and its implications for organized crime are explained. An original method for measuring harm is proposed.